ZUM Magazine: excitement in Brazil’s cultural scene - Pereira, Flavya Mutran (PORTO ARTE: Revista de Artes Visuais, 2018)
This is a review of ZUM, a semiannual magazine published by the Moreira Sales Institute. Aspects such as production, distribution, editorial line and the importance of the publication in Brazil’s art and culture scene will be addressed under a critical and historical approach.